Five-year Contraceptive Use of 52-mg Levonorgestrel Releasing Intrauterine System in Young Women, Menstrual Patterns, and New Contraceptive Choice - Elaine Cristina Fontes de Oliveira; Ana Luiza Lunardi Rocha (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective To evaluate the continuation rates of the 52-mg levonorgestrel-releasing intrauterine system (LNG-IUS) during the first 5 years of use, reasons for its discontinuation, bleeding patterns, and new contraceptive choice after the 5th year, in adolescents and young women. Methods The present study was a 5-year prospective cohort conducted in a Family Planning Service of a tertiary hospital in Brazil. We selected 100 healthy women between 15 and 24 years old who used 52-mg LNG-IUS for contraception. The clinical follow-up of these women took place from June 2017 to December 2022. The study evaluated the continuation rates of the method, reasons for its discontinuation, bleeding patterns, and new contraceptive choice after the 5th year. Continuous data were reported as mean ± standard deviation (SD) and range (minimum-maximum). Categorical variables were described as percentages. Results The continuation rates of LNG-IUS were 89.1% (82/92), 82.9% (72/87), 75.3% (64/85), 70.5% (60/85), and 64.2% (54/84) in the 1st, 2nd, 3rd, 4th, and 5th years of use, respectively. The main reason for discontinuation was acne (11/30). Amenorrhea rates were 50, 54.1, 39, 35.7, and 51.8% at 12, 24, 36, 48, and 60 months, respectively. All patients who completed the study and needed contraception after the 5th year opted for long-acting contraceptive methods (LARC). Conclusion The LNG-IUS showed high continuation rates in adolescents and young women in the first 5 years of use. Most patients who completed the study chose a LARC method after the 5th year.